Finansmana erişimde katılım bankacılığının kullanımı: Diyarbakır ili üzerine bir araştırma - Akkaya, Cihan (My University, 2022)
İslami Bankacılık İslam'ın emirlerine uyan yasaklarından sakınan, Kur'an ve hadislerle çelişmeyen kâr-zarar ortaklığına dayanan finansal sistemdir. Faiz nedeniyle meydana gelen aşırı borçlanma dünyada büyük ekonomik krizlere zemin hazırlamaktadır. İslami finansal sistemlerin temelinde üretim ve ticaret olduğu için faizden kaynaklı ekonomik krizlerde bir nebze de olsa sistemi koruyabilmektedir. Bu nedenle İslami Bankacılık dünyada kendi içinde çok hızlı bir gelişme göstermiştir. Bu gelişme ışığında İslami bankacılık faaliyetleri hem artmakta hem de çeşitlenmektedir. Çalışmada ülkemizde Katılım Bankaları olarak faaliyet gösteren bu kuruluşların, üretim odaklı faaliyet gösteren firmalarla finansal ilişkileri ve Diyarbakır Organize Sanayi Bölgesinde faaliyet gösteren firmaların finansmana erişimde Katılım Bankacılığının rolü araştırılmıştır. Çalışmada veriler, yüz yüze yapılan anket yöntemi ile firmaların Katılım Bankalarının hangi finansman yöntemlerini kullandığı, karşılaştıkları finansal sorunların neler olduğu, firmaların Katılım Bankası algısı ve Katılım Bankalarının tercih nedenleri araştırılmıştır. Elde edilen veriler SPSS 26.0programı ile analiz edilmiştir. Anahtar Kelimeler: Katılım Bankacılığı, İslami Finans, Diyarbakır Organize Sanayi Bölgesi, Finansal Katılım Araçları, Küçük ve Orta Büyüklükteki İşletmeler

Islamic banking is a financial system that abides by the orders of Islam, avoids the prohibitions, and is based on profit-loss sharing that does not contradict the Qur'an and hadiths. The excessive borrowing due tointerest paves the way for major economic crisesin the world. Since the basis of Islamic financial systemsis production and trade, it can protect the system to some extent in economic crises caused by interest. This, in turn, can protect the Sistem to some extent in economic crises caused by interest. For this reason, Islamic Banking has shown a very rapid in it self development in the world. In the light of this development, Islamic banking activities are both increasing and diversifying. In the study, the financial relations of these institutions operating as participation banks in our country with productionoriented companies and the roleof participation banking in access to finance of companies operating in Diyarbakır Organized Industrial Zone were investigated. In the study, the data, which financing methods the participation banks use, the financial problems they encounter, the perception of the participation banks of the companies and the reasons for the preference of the participation banks were investigated with the face-to-face survey method. It was obtained and analyzed with SPSS 26.0 analys is program. Keywords: Participation banking, Islamic Finance, Diyarbakir Organized Industrial Zone, Financial Participation Tools, Small and Medium Enterprises
Using participation banking to access finance: A research on the province of Diyarbakır
Keywords: Maliye; Finance; İşletme; Business Administration